Photonic Methods Applied to Heritage Conservation in Argentina - Morita, María Mercedes (2017)
As part of an ongoing program performed in collaboration with museums and institutions of Argentina, we present results on the application of laser based techniques and 3D imaging methods for material characterization, cleaning and documentation of cultural heritage objects, particularly the collections of public museums located in different regions of the country. In this work, we present results on the application of Laser Induced Breakdown Spectroscopy (LIBS) for material characterization of objects found in the ex-detention, torture and extermination center called Club Atletico (Instituto Espacio Memoria) of Buenos Aires. We also show laser cleaning applications to archaeological objects found in Patagonia and in the city of Buenos Aires. Finally, we present a 3D system developed for recording and documentation of artworks. It is based on digital photogrammetry and uses low cost devices and free software for data processing. This 3D system has measurement tools and thepossibility of creating deterioration maps in the virtual model. We present examples of the applications of this 3D system to artworks from argentine museums.